Industrial training report: Perbadanan Perpustakaan Awam Selangor (Pustaka Raja Tun Uda) / Muhammad Irfan Abd Munir - Abd Munir, Muhammad Irfan (Perpustakaan Tengku Anis, 2019)
The trainee internship at Perbadanan Perpustakaan Awam Selangor (PPAS) started from 1st February 2019 until 28th June 2019. During the internship program the trainee are involve in all department rather than involve in IT department only. Besides, the trainee also acknowledges in every department give different view of each department responsibilities. Moreover, the trainee also have involve in several activity which is organize program for school holidays, Pesta Buku Selangor and rebranding of library. Next, the trainee chooses to develop a guideline video as a special project. The reasons choose to develop the video it to ensure the user aware about the knowledge in using the reference material. The trainee also learns something new during internship program and also can implements the knowledge that learns at faculty towards internship program.